Development of a Tri Dharma Database System for the Culinary Education Study Program - Fatma Tresno Ingtyas; Dina Ampera; ST Wahidah; Ismail Jahidin; Yudhistira Anggraini (Sakura Digital Nusantara, 2026)
Purpose: This study aimed to develop and evaluate a Tri Dharma-based database system to improve document management and administrative services in the Culinary Education Study Program at State University of Medan. Methods: This study employed a Research and Development (R&D) approach using a modified Borg and Gall development model combined with a prototype approach. The study involved 23 participants, consisting of two information system experts, one media expert, and twenty prospective users (lecturers and administrative staff) who participated in the validation and user evaluation processes. Data were collected through observations, interviews, expert validation sheets, and user response questionnaires and analyzed using descriptive statistics. Findings: The developed database system obtained a mean feasibility score of 4.00 from the information system experts, 4.40 from the media expert, and 4.33 from users. These findings indicate that the system is feasible, user-friendly, and effective in supporting the management of Tri Dharma activities, improving document organization, and facilitating academic administration at the study program level. Research Implications: The database system can be implemented as an administrative management tool to improve document organization, support accreditation activities, and strengthen data management practices within higher education institutions. Originality: This study presents an integrated database system specifically designed to manage education, research, community service, and supporting academic activities within a study program, providing a practical model that can be adapted by other higher education institutions.